2020
DOI: 10.3390/nano10020343
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fatty Acids and BSA Purity on Synthesis and Properties of Fluorescent Gold Nanoclusters

Abstract: Fluorescent gold nanoclusters (AuNCs) are envisaged as a novel type of fluorophores. This work reports on the first comparative study investigating the effect of presence/absence/abundance of fatty acids (namely palmitic acid, PA) or other substances (like glycoproteins and globulins) in the protein (bovine serum albumin, BSA) on synthesis and properties of the final AuNCs. The most popular template (BSA) and microwave (MW)-assisted synthesis of AuNCs have been intentionally chosen. Our results clearly demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…Since AuBSA-Fe nanocomposites are prepared by a synthetic approach obeying the principles of green chemistry (i.e., non-toxic reactants and aqueous environments, no abundant chemicals used), their biocompatibility can be presumed. Moreover, AuBSA nanocomposites have been tested by many authors, including us [ 19 ], for potential cytotoxicity, which was revealed to be negligible. Similarly, SPIONs were tested by several authors and manifested almost zero cytotoxicity (e.g., [ 25 , 26 , 27 , 28 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since AuBSA-Fe nanocomposites are prepared by a synthetic approach obeying the principles of green chemistry (i.e., non-toxic reactants and aqueous environments, no abundant chemicals used), their biocompatibility can be presumed. Moreover, AuBSA nanocomposites have been tested by many authors, including us [ 19 ], for potential cytotoxicity, which was revealed to be negligible. Similarly, SPIONs were tested by several authors and manifested almost zero cytotoxicity (e.g., [ 25 , 26 , 27 , 28 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Aside from the complexity of the preparation, the individual syntheses of NSs also differ in the total preparation time, ranging from a few minutes (in the case of microwave-assisted synthesis) [ 19 , 20 , 21 ] to tens of hours [ 7 , 15 , 18 ]. Today, simplicity, reproducibility, and green chemistry in NSs preparation are beneficial and highly recommended and are therefore applied in this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve luminescent properties of our previously prepared AuNCs [24] [25], we started to synthesize GSNC samples in a very similar way (Figure 1 here and compare experimental sections here with that in [25]).…”
Section: De Nitions Of Synthesis and Maturing; Samples Labellingmentioning
confidence: 99%
“…Changes of protein secondary structure CD spectra were measured for all six metallic samples, their three references (BSA-T), and natural BSAthey are shown in Figure SI-2 in Supporting Information. Using BeStSel program (as in our previous work [24]), the percentage contents of α-helices, anti-/parallel structures, turns and others were evaluated. Then, Table 2 clearly summarizes the percentage contents of each structural arrangement of the protein scaffold within our metallic as well as non-metallic samples.…”
Section: Metallic Part Characterization (Icp-ms Xps Uv-vis Absorption)mentioning
confidence: 99%